HUBUNGAN ANTARA LUNG CAPACITY DENGAN DERAJAT DYSPNEA SEBAGAI PREVENTIF ISPA BERULANG - Raju Rizqi Ananda; Siti Rahmalia; Ari Pristiana Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Acute respiratory infection (ARI) is an acute infection that attacks one part of the nasal passage through the alveoli including the adnexa. One of the manifestations of ARI is dyspnea. Dyspnea is caused by airway obstruction. The degree of obstruction in the respiratory tract can be measured using spirometry. This study aims to determine the relationship between lung capacity and degree of dyspnea as preventive of recurrent ARI. This study used descriptive correlation with cross sectional approach. This study was conducted in work area of Harapan Raya Public Health Center with 78 samples which selected using purposive sampling technique with inclusion criteria. The instruments were used questionnaires and spirometry. Data was analysed by using univariate analysis and bivariate by using Chisquare test. The results of this study showed that is significant relationship between lung capacity and degree of dyspnea as preventive of recurrent ARI with p value (0,003) < α (0,05). The results of this study indicate that lung capacity affects the degree of dyspnea. It is recommended for health workers to promote lung capacity check and provide education to treatment of dyspnea among patients with ARI. Keywords: ARI, dyspnea, lung capacity